Bone‐targeted delivery of TGF‐β type 1 receptor inhibitor rescues uncoupled bone remodeling in Camurati–Engelmann disease. Issue 1 (9th August 2018) - Qin, Yunhao; Tang, Shibing; Zhen, Gehua; Ding, Qiang; Ding, Sheng; Cao, Xu
Abstract: Camurati–Engelmann disease (CED) is a genetic bone‐modeling disorder mainly caused by mutations in the gene that encodes transforming growth factor‐β1 (TGF‐β1). Symptoms of CED include bone pain, fractures, and dysplasia. Currently, effective therapies for bone fracture and dysplasia in CED are urgently needed. We have demonstrated that TGF‐β1 is a coupling factor for bone remodeling and is aberrantly activated in CED. Daily injection of TGF‐β type 1 receptor inhibitor (TβR1I) attenuated CED symptoms, but this systemic administration caused serious side effects. In this study, we created a conjugate linking TβR1I and alendronate, which delivered TβR1I specifically to bone. After weekly injection of the conjugate for 8 weeks, normal bone morphology and remodeling in CED mice was maintained with a minimum effective dose 700 times lower than TβR1I injection. Additionally, we found that the conjugate restored normal bone turnover by reducing the number of osteoblasts and osteoclasts, maintained a regular osteogenic microenvironment by regulating the formation of CD31 and Endomucin double‐positive vessels, and preserved ordinary bone formation via inhibition of the migration of leptin‐receptor‐positive cells. Thus, targeting delivery of TβR1I to bone is a promising therapy for CED and other uncoupled bone remodeling disorders. Abstract : Camurati‐Engelmann disease (CED) is a genetic bone‐modeling disorder mainly caused by mutations in the gene for transforming growth factor‐β1 (TGF‐β1). This causes the protein to be aberrantly activated, which disrupts the coupling between bone resorption and formation. Systemic administration of TGF‐β type 1 receptor inhibitor (TβR1I) attenuates CED symptoms, but causes serious side effects. This study demonstrates that a novel conjugate delivering TβR1I directly to bone is a more effective therapy for CED.